RASIONALITAS PENERIMAAN BANTUAN PERMAKANAN BAGI PENYANDANG DISABILITAS MENENGAH KEBAWAH DI KOTA SURABAYA - Ivandi, Rizal Ramadhan (Paradigma, 2022)
People with disabilities are one of the minority groups in social life. In people’s lives, people with disabilities, especially those belonging to low-income communities, are considered as people who have abnormalities or limitations (the weak) in their daily lives. This study uses the rationality choice theory of James Coleman. The research method used in this study is qualitative with a rational choice approach by James Coleman. The result of this study is that in receiving food assistance, persons with disabilities have different opinions or perceptions regarding the provision of food assistance. The reasons people with disabilities receive assistance are: respecting the good intentions of the government, reducing the cost of living and the burden on families, as well as increasing nutritional intake. However, in its implementation, there are often problems felt by beneficiaries, namely persons with disabilities. In following up on their problems, some people with disabilities did not report the incident due to an understanding that government assistance must be received and some tried to report their findings to the authorities. Keywords: Rationality, Disability, Food Assistance